Aestheticism and Decoration: At Home with Michael Field - Ana Parejo Vadillo (Cahiers Victoriens et Edouardiens)
Talia Schaffer’s work on the poet Rosamund Marriott Watson and her theories of home decoration has been key to understand how female aesthetes reconfigured and re-appropriated this aspect of aestheticism. Looking at the aesthetic writings of Marriott Watson’s The Art of the House, Schaffer has shown how she forged a new, complex version of aestheticism by both aligning herself with male aesthetes in their critique of women’s arts and crafts tradition and distancing herself from male aestheticism by re-articulating an aesthetic of the home embedded in feminine décor.But how did female aesthetes inhabit and live that aestheticism We know nothing of how Watson’s theories informed her own life as an aesthete. For this reason the case of Michael Field is particularly important. Michael Field never wrote on home decoration, but an examination of Bradley and Cooper’s diaries, letters and photographs reveal their unique approach to the house beautiful movement. As they put it in their diary, Works and Days: “To-day’s dreams & desires—the tongs with wh. the angel makes living coals of our lips to-day—these are the things to be expressed in our walls, in our furniture, in our dress.” This expressive, living aestheticism is at the core of this essay.